EFEKTIVITAS AUDIO VISUAL DALAM MENINGKATKAN MINAT BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Nur Khosiah; Muhammad Syahid Syafa’at; Asripa Asripa (LPPM STAI Muhammadiyah Probolinggo, 2022)
Learning media is an important part in the world of education. Through learning media, educators can build student excellence in realizing learning goals to the fullest. By utilizing this learning media, it can provide unlimited advantages in learning, because it will make it easier for a teacher to provide explanations to students so that students more easily understand the subjects given. The purpose of this study was to increase students' interest in learning in PAI subjects through audio-visual media for class X at SMA Darul akhlak Ambulu, Sumberasih District, Probolinggo Regency. The configuration of the exam used is Classroom Action Research (CAR) which is expected to increase student interest in learning towards students in class X SMA Darul Akhlaq. From cycle I and cycle II, it can be seen that some students who were initially less interested and less interested in PAI subjects, are now very enthusiastic through audio-visual media. It can be seen that the effective level is at 80% and ineffective at 20%, resulting in an expanded level to be real, in the primary cycle of 40%, the second cycle of 80%.